Happiness, trust, and social relationships: The social dimensions of urban quality of life in Debrecen - Czibere, Ibolya (Central European Journal of Educational Research, 2026)
The study of happiness and quality of life in urban settings has become increasingly prominent in both international and domestic social science research. The quality of social relationships and the level of trust are among the key determinants of subjective well-being. This study aims to explore the relationships between happiness, trust, and social ties among the urban population of Debrecen, and to examine how these vary across different demographic groups. The analysis is based on a representative sample of 500 respondents from the “Debrecen 2025” survey, using questionnaire-based data collection. The findings indicate that the subjective well-being of Debrecen’s residents is generally favourable and closely associated with the quality of their social relationships. In particular, family and friendship ties, as well as levels of trust, show consistent associations with life satisfaction. At the same time, it is not the quantity of social ties, but their quality, that proves to be decisive. No significant gender differences were found, whereas notable variations emerge across age groups and levels of educational attainment: older individuals and those with higher levels of education tend to report higher levels of well-being and trust. The results confirm the importance of social capital in shaping urban quality of life and suggest that strengthening social relationships and fostering trust may play a key role in improving overall well-being.